Determining of tourists' experience revisit intention to architectural mosques in Kuala Lumpur. - Md Baliya, Nur Zafirah; Saad, Mazni (2020)
Malaysia has been recognized as one of the destinations for Muslim travellers, possessing factors such as multicultural identities, a unique culture and heritage based on Islamic principles. In Kuala Lumpur, most iconic Islamic attractions, the National Mosque and Federal Mosque are must- visit locations in the city. These mosques are highly promoted by the government since undergoing an increase in tourists’ arrival. Thus, it is important to acknowledge the success of tourism destination attractions depends heavily on many factors, including the worthiness for repeat visitation. This research aims to examine the relationship on tourists’ experiences effect on revisiting intention in architectural mosques in Kuala Lumpur. The number of respondents in this research is 166 people that have been engaged with any architectural mosques located in Kuala Lumpur. The outcome revealed that attachment, social interaction and aesthetic value are the experiences that affect tourists’ revisit intention.